An All‐Organic Semiconductor C3N4/PDINH Heterostructure with Advanced Antibacterial Photocatalytic Therapy Activity. Issue 33 (25th June 2019) - Wang, Longwei; Zhang, Xiao; Yu, Xin; Gao, Fene; Shen, Ziyi; Zhang, Xiaolei; Ge, Shenguang; Liu, Jing; Gu, Zhanjun; Chen, Chunying
Abstract: Antibacterial photocatalytic therapy has been reported as a promising alternative water disinfection technology for combating antibiotic‐resistant bacteria. Numerous inorganic nanosystems have been developed as antibiotic replacements for bacterial infection treatment, but these are limited due to the toxicity risk of heavy metal species. Organic semiconductor photocatalytic materials have attracted great attention due to their good biocompatibility, chemically tunable electronic structure, diverse structural flexibility, suitable band gap, low cost, and the abundance of the resources they require. An all‐organic composite photocatalytic nanomaterial C3 N4 /perylene‐3, 4, 9, 10‐tetracarboxylic diimide (PDINH) heterostructure is created through recrystallization of PDINH on the surface of C3 N4 in situ, resulting in enhanced photocatalytic efficiency due to the formation of a basal heterostructure. The absorption spectrum of this composite structure can be extended from ultraviolet to near‐infrared light (750 nm), enhancing the photocatalytic effect to produce more reactive oxygen species, which have an excellent inactivation effect on both Gram‐negative and positive bacteria, while demonstrating negligible toxicity to normal tissue cells. An efficient promotion of infectious wound regeneration in mice with Staphylococcus aureus infected dermal wounds is demonstrated. This all‐organic heterostructure shows great promise for use in wound disinfection. Abstract : An all‐organic metal‐free semiconductor C3 N4 /PDINH heterostructure with advanced antibacterial photocatalytic therapy activity is demonstrated. The formation of the heterostructure can extend the spectrum utilization range to 750 nm, which produces more ROS under light illumination and acts on bacteria‐infected skin. This eliminates the inflammation of the affected area and enables wounds to be cured quickly.